Understanding religious conversion - Rambo, Lewis R. (Lewis Ray), 1943- (New Haven : Yale University Press, 1993)
Looking at a wide variety of religions, this work offers an exploration of religious conversion. The phenomena is approached from a variety of disciplines, including psychology, sociology, theology and anthropology.
Models and methods -- Context -- Crisis -- Quest -- The advocate -- The advocate's strategy -- Encounter between advocate and convert -- Interaction -- Commitment -- Consequences.
Includes bibliographical references (p. 209-234) and index.
Keywords: Conversion.-- Religious Conversions